A water quality improvement device with layered loading of solid composite carbon source and suspended filler and its application
By using the design of layered loaded solid composite carbon source and suspended filler in the water quality enhancement device, and using the technology of porous sustained release carrier and switch polymer, the problems of insufficient membrane hanging speed and water treatment efficiency of the existing water quality enhancement device are solved, and efficient water treatment and reuse of solid composite carbon source are achieved.
Patent Information
- Application Number
- CN202310433848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-04-21
AI Technical Summary
The existing water quality enhancement devices have shortcomings in membrane hanging speed and water treatment efficiency, and the use of traditional biological fillers requires long-term debugging and intercepting systems to prevent contaminants from entering the subsequent treatment procedures.
A water quality lifting device with layered loading of solid composite carbon sources and suspension fillers is used to achieve sustained release and reuse of nutrients by loading solid composite carbon sources in the inner ball cage and loading suspended fillers in the outer ball cage.
The microbial membrane hanging speed and water treatment efficiency are improved, and the reuse of solid composite carbon sources and the long-term maintenance of the nutritional sustained release effect are achieved.
Smart Images

Figure CN116444043B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a water quality improvement device for layered loading of solid composite carbon sources and suspended fillers and application thereof. Background Art
[0002] Biofilm water treatment technology is a method of water treatment using microbial films attached and grown on certain solid surfaces. It has the advantages of high treatment efficiency, stable operation, low sludge production, and no secondary pollution. Biological fillers play an important role in biofilm water treatment technology. They can provide a place for microorganisms to attach and grow and reproduce, increase the biomass of microorganisms, enrich their species, and improve the shock load resistance of water treatment systems. Some biological fillers can also slowly release nutrients during use to promote the growth and reproduction of beneficial microorganisms. However, traditional bulk biological fillers have a slow biofilm growth rate, and the initial debugging time is long when used for water treatment. In addition, an interception system needs to be set up to prevent them from entering the subsequent water treatment procedures, resulting in a decrease in the efficiency of microbial water treatment and the efficiency of subsequent water treatment procedures.
[0003] The patent with application number CN202222250201.X discloses a biological filler for integrated sewage treatment equipment, including a mesh upper hemispherical shell and a lower hemispherical shell, which are detachably connected, and a plurality of water-permeable mesh holes are respectively provided on the upper hemispherical shell and the lower hemispherical shell. After the upper hemispherical shell and the lower hemispherical shell are buckled and connected, a spherical cavity is formed inside, and an activated carbon filler is arranged in the spherical cavity. The activated carbon filler can provide a matrix for microbial biofilm and improve the removal efficiency of wastewater pollutants through adsorption; the spherical shell can intercept the activated carbon filler to prevent it from entering the subsequent water treatment procedure, and the upper and lower hemispherical shells are connected by a detachable snap-on connection, so that the activated carbon filler can be replaced, and multiple disassembly and recycling can be achieved. However, although this single-layer ball device can also load solid composite carbon sources and suspended fillers at the same time, it is difficult to make the two cooperate well, and then fully integrate the functions of the two, and the filler biofilm speed and water treatment efficiency are limited. Summary of the invention
[0004] In order to solve the technical problems of limited biofilm growth speed and water treatment efficiency of existing water quality improvement devices, the present invention provides a water quality improvement device with layered loading of solid composite carbon source and suspended filler. The water quality improvement device can fully integrate the functions of suspended filler and solid composite carbon source, improve biofilm growth speed and water treatment efficiency; and the solid composite carbon source therein can be reused and has a good nutrient slow release effect.
[0005] The specific technical scheme of the present invention is:
[0006] In the first aspect, the present invention provides a water quality improvement device with layered loading of solid composite carbon sources and suspended fillers, comprising an inner ball cage and an outer ball cage; the inner ball cage is arranged in the outer ball cage, and a plurality of through holes are distributed on the inner ball cage and the outer ball cage, and the inner ball cage and the outer ball cage are both openable and closable spheres; the solid composite carbon source is loaded in the inner ball cage; the suspended filler is loaded between the inner ball cage and the outer ball cage; the solid composite carbon source comprises a porous slow-release carrier, nutrients loaded in the porous slow-release carrier and a switch polymer grafted on the outside of the porous slow-release carrier; the two ends of the switch polymer are a free end and a fixed end respectively; the fixed end is poly (N-isopropylacrylamide) grafted on the porous slow-release carrier.
[0007] In the water quality improvement device of the present invention, the suspended filler of the outer layer (loaded in the outer ball cage) can provide a place for the attachment and growth and reproduction of microorganisms, and the solid composite carbon source of the inner layer (loaded in the inner ball cage) can slowly release nutrients, which, in the process of diffusing outward, contact with the suspended filler, promote the growth and reproduction of beneficial microorganisms therein, form biofilms, and promote microbial metabolism to decompose pollutants in water. In the above manner, the suspended filler and the solid composite carbon source are brought together and made relatively independent and closely combined, so that the two can better cooperate in function, thereby improving the biofilm speed and water treatment efficiency.
[0008] The present invention uses a special solid composite carbon source, which has a good sustained release effect, and the nutrient sustained release carrier therein can be reused, that is, after failure (the loaded nutrients are gradually consumed and the release amount is insufficient), it can be reloaded with nutrients and maintain good sustained release performance. The specific mechanism is as follows: The present invention grafts a switch polymer on the outside of the porous sustained release carrier, and the poly N-isopropylacrylamide chain therein has a reversible temperature response characteristic. When water treatment is carried out at 30°C or below, the poly N-isopropylacrylamide chain is in an extended state, which can close the pores on the porous sustained release carrier and slowly release the nutrients; when nutrients are loaded at 38°C or above, the poly N-isopropylacrylamide chain shrinks, opening the pores on the porous sustained release carrier, so that the nutrients can be adsorbed into the porous sustained release carrier, completing the loading of nutrients.
[0009] Preferably, the free end of the switch polymer is a copolymer of N-isopropylacrylamide and 4-vinylpyridine.
[0010] By doping 4-vinylpyridine at the free end of the switch polymer, the loading of nutrients in the porous slow-release carrier can be promoted without affecting the slow-release performance of the solid composite carbon source. Specifically: when water treatment is carried out in an environment with a pH of ≥5.0, the nitrogen atoms in the pyridine group are uncharged and will not generate electrostatic repulsion between the molecular chains of the switch polymer, thereby not having an excessive impact on the entanglement between the molecular chains of the switch polymer, which is beneficial for the switch polymer to close the pores on the porous slow-release carrier and achieve the slow release of nutrients; when nutrients are loaded in an environment with a pH of ≤4.2, the nitrogen atoms in the pyridine group are positively charged and can generate electrostatic repulsion between the molecular chains of the switch polymer, promoting the disentanglement between the molecular chains of the switch polymer, thereby being beneficial for the loading of nutrients; in addition, the present invention dopes 4-vinylpyridine at the free end of the switch polymer instead of the middle, which can avoid the electrostatic repulsion inside the molecular chain of the switch polymer when loading nutrients, thereby preventing the molecular chain from shrinking.
[0011] Preferably, the method for preparing the solid composite carbon source comprises the following steps:
[0012] (1) Grafting -COC(CH3)2Br groups onto the surface of a porous sustained-release carrier to obtain a brominated porous sustained-release carrier;
[0013] (2) After mixing the brominated porous sustained-release carrier, the polymerization catalyst, the ligand and the solvent III, N-isopropylacrylamide is added under the protection of an inert gas, and the mixture is reacted at 30 to 40° C. for 2 to 2.5 hours, and then 4-vinylpyridine is added, and the mixture is reacted at 30 to 40° C. for 15 to 20 minutes, and the product is separated to obtain a nutrient sustained-release carrier;
[0014] (3) After the nutrients are prepared into a solution, the pH is adjusted to no higher than 4.2, the temperature is raised to no lower than 38° C., a nutrient slow-release carrier is added thereto, the temperature is maintained at no lower than 38° C. for immersion, and then the pH is adjusted to no lower than 5.0, and the temperature is lowered to no higher than 30° C., the product is separated, and a solid composite carbon source is obtained.
[0015] In steps (1) and (2), after the -COC(CH3)2Br group is grafted onto the surface of the porous sustained-release carrier, a free radical polymerization reaction can be initiated to graft a switch polymer having a fixed end of poly N-isopropylacrylamide and a free end of isopropylacrylamide-vinylpyridine copolymer onto the surface of the porous sustained-release carrier.
[0016] In step (3), at pH ≤ 4.2 and temperature ≥ 38°C, the pyridine group at the free end of the switch polymer is positively charged, and the poly (N-isopropylacrylamide) molecular chain shrinks, so that the pores on the porous sustained-release carrier are opened, and the nutrients can be loaded into the porous sustained-release carrier more quickly; after the loading is completed, the pH is adjusted to not less than 5.0, and the temperature is lowered to not more than 30°C. At this time, the pyridine group is not charged, the poly (N-isopropylacrylamide) molecular chain stretches, and the pores on the porous sustained-release carrier are closed, so that the nutrients can be slowly released when the water quality improvement device is used.
[0017] Preferably, in step (2), the mass ratio of the brominated porous sustained-release carrier, N-isopropylacrylamide and 4-vinylpyridine is 1:1.5-2.0:0.1-0.2.
[0018] Preferably, in step (2), the mass ratio of the brominated porous sustained-release carrier, the polymerization reaction catalyst and the ligand is 1:0.3-0.5:0.6-0.8.
[0019] Preferably, the specific process of step (1) comprises the following steps:
[0020] (1.1) utilizing the hydroxyl groups on the surface of the porous sustained-release carrier to graft the aminosilane coupling agent onto the surface of the porous sustained-release carrier;
[0021] (1.2) Using the aminated porous sustained-release carrier and 2-bromoisobutyryl bromide as raw materials, a substitution reaction between the amino group and 2-bromoisobutyryl bromide is carried out to obtain a brominated porous sustained-release carrier.
[0022] Preferably, the specific process of step (1.1) includes the following steps: mixing the aminosilane coupling agent with solvent I, hydrolyzing the mixture, and then adding the porous sustained-release carrier thereto, reacting at 70 to 80° C. for 2 to 4 hours, separating the product, and obtaining an amino-porous sustained-release carrier.
[0023] Furthermore, in step (1.1), the mass ratio of the porous sustained-release carrier, the aminosilane coupling agent and the solvent I is 1:0.7-1.4:3-10.
[0024] Preferably, the specific process of step (1.2) includes the following steps: mixing 2-bromoisobutyryl bromide, an acid binding agent and a solvent II, adding an amino-modified porous sustained-release carrier thereto, reacting at 0 to 5° C. for 4 to 6 hours, separating the product, and obtaining a brominated porous sustained-release carrier.
[0025] Furthermore, in step (1.2), the mass ratio of the amino-modified porous sustained-release carrier, 2-bromoisobutyryl bromide, acid-binding agent and solvent II is 1:0.8-2.0:1.6-4.0:5-10.
[0026] Preferably, the method for preparing the porous sustained-release carrier comprises the following steps: adding water glass solution to a filler mixture comprising fly ash, kaolin and zeolite powder, mixing, granulating and calcining to obtain a porous sustained-release carrier.
[0027] The porous slow-release carrier prepared by the above method can utilize its porous structure to load more nutrients, and utilize the adsorption effect of the porous slow-release carrier and the switch polymer grafted on its surface to achieve slow release, which can make the solid composite carbon source have a longer effective period - according to tests, the water quality improvement device of the present invention can be effective for up to six months after one deployment.
[0028] Furthermore, the mass ratio of the fly ash, kaolin, zeolite powder and water glass is 5-7:3-5:2-4:3-4.
[0029] Furthermore, the mass fraction of the water glass solution is 30-40%.
[0030] Furthermore, the calcination temperature is 400-500° C. and the calcination time is 2-3 hours.
[0031] Preferably, the nutrients include the following components by weight: 25-35 parts of polyhydroxybutyrate valerate (PHBV), 65-75 parts of acetate starch, 15-25 parts of butyric acid, 4-8 parts of MnSO4, 4-8 parts of MgSO4, 2-5 parts of ZnSO4, 0.01-0.05 parts of CuSO4, 0.2-0.4 parts of KI, and 0.01-0.03 parts of CaCl2.
[0032] The above-mentioned nutrient formula contains carbon sources with different release rates, multiple trace elements and microbial growth promoters, which can promote the growth and reproduction of nitrifying bacteria and denitrifying bacteria, achieve simultaneous nitrification and denitrification, and improve the total nitrogen removal effect.
[0033] Preferably, the inner ball cage is an openable and closable sphere composed of an inner upper ball cage and an inner lower ball cage, and the outer ball cage is an openable and closable sphere composed of an outer upper ball cage and an outer lower ball cage; an annular upper partition net and a lower partition net are provided between the outer upper ball cage and the outer lower ball cage; the outer ring side and the inner ring side of the upper partition net are respectively connected to the inner wall of the outer upper ball cage and the outer wall of the inner upper ball cage; the outer ring side and the inner ring side of the lower partition net are respectively connected to the inner wall of the outer lower ball cage and the outer wall of the inner lower ball cage.
[0034] Preferably, the suspended filler is MBBR filler.
[0035] MBBR filler has the advantages of large specific surface area, good hydrophilicity, strong wear resistance, and good permeability. It can maintain a fluidized state well under the action of aeration, which is conducive to the contact and degradation of pollutants with microbial membranes.
[0036] In a second aspect, based on the same technical concept, the present invention provides the application of the water quality improvement device in microbial water treatment.
[0037] Preferably, the application comprises the following steps: placing the water quality improvement device into a water treatment device, performing water treatment after biofilm formation, and controlling the temperature to be no higher than 30°C and the pH to be no lower than 5.0 during the biofilm formation and water treatment process; when the water treatment efficiency decreases, taking out the solid composite carbon source in the water quality improvement device, reloading the nutrient substance according to step (3) (i.e., step (3) in the preparation method of the solid composite carbon source described above), then loading the water quality improvement device into the water treatment device, and placing the water quality improvement device into the water treatment device again for water treatment.
[0038] Compared with the prior art, the present invention has the following advantages:
[0039] (1) The present invention loads the solid composite carbon source and the suspended filler into the inner layer and the outer layer respectively, so that the two can cooperate well in function, accelerate the biofilm formation speed of the filler, and improve the water treatment efficiency;
[0040] (2) The solid composite carbon source used in the present invention can achieve a good sustained release effect by grafting a specially prepared switch polymer on a porous sustained release carrier, and it can be reloaded with nutrients after failure, thereby realizing the reuse of the nutrient sustained release carrier. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 A model diagram of the water quality improvement device of the present invention (the inner and outer ball cages are in an upper and lower closed state);
[0042] Figure 2 A model diagram of the water quality improvement device of the present invention (the inner and outer ball cages are in the upper and lower open states). DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the embodiments.
[0044] Overall embodiment
[0045] A water quality improvement device loaded with a layered solid composite carbon source and a suspended filler, comprising an inner cage and an outer cage; the inner cage is arranged in the outer cage, both of which are provided with a plurality of through holes, and both are openable and closable spheres; the inner cage is loaded with a solid composite carbon source; a suspended filler is loaded between the inner cage and the outer cage; the solid composite carbon source comprises a porous slow-release carrier, nutrients loaded in the porous slow-release carrier and a switch polymer grafted on the outside of the porous slow-release carrier; the two ends of the switch polymer are a free end and a fixed end respectively; the fixed end is poly (N-isopropylacrylamide) grafted on the porous slow-release carrier.
[0046] In some specific embodiments, the free end of the switch polymer is a copolymer of N-isopropylacrylamide and 4-vinylpyridine.
[0047] In some specific embodiments, the method for preparing the solid composite carbon source comprises the following steps:
[0048] (1) Grafting -COC(CH3)2Br groups onto the surface of a porous sustained-release carrier to obtain a brominated porous sustained-release carrier;
[0049] (2) After mixing the brominated porous sustained-release carrier, the polymerization catalyst, the ligand and the solvent III, under the protection of an inert gas, N-isopropylacrylamide is added, and the reaction is carried out at 30 to 40° C. for 2 to 2.5 hours, and then 4-vinylpyridine is added, and the reaction is continued at 30 to 40° C. for 15 to 20 minutes, and the product is separated to obtain a nutrient sustained-release carrier; the mass ratio of the brominated porous sustained-release carrier, N-isopropylacrylamide (NIPAAm), 4-vinylpyridine (4VP), the polymerization catalyst and the ligand is 1:1.5 to 2.0:0.1 to 0.2:0.3 to 0.5:0.6 to 0.8;
[0050] (3) After the nutrients are prepared into a solution, the pH is adjusted to no higher than 4.2, the temperature is raised to no lower than 38° C., a nutrient slow-release carrier is added thereto, the temperature is maintained at no lower than 38° C. for immersion, and then the pH is adjusted to no lower than 5.0, and the temperature is lowered to no higher than 30° C., the product is separated, and a solid composite carbon source is obtained.
[0051] In some specific embodiments, the specific process of step (1) includes the following steps:
[0052] (1.1) After mixing the aminosilane coupling agent and the solvent I, hydrolyzing them at 40-50° C. for 0.5-1.5 h, then adding the porous sustained-release carrier thereto, reacting at 70-80° C. for 2-4 h, separating the product, and obtaining an amino-modified porous sustained-release carrier; the mass ratio of the porous sustained-release carrier, the aminosilane coupling agent, and the solvent I is 1:0.7-1.4:3-10;
[0053] (1.2) 2-bromoisobutyryl bromide, an acid binding agent and a solvent II are mixed, an aminated porous sustained-release carrier is added thereto, the mixture is reacted at 0 to 5° C. for 4 to 6 hours, a product is separated, and a brominated porous sustained-release carrier is obtained; the mass ratio of the aminated porous sustained-release carrier, 2-bromoisobutyryl bromide, an acid binding agent and a solvent II is 1:0.8 to 2.0:1.6 to 4.0:5 to 10.
[0054] In some specific embodiments, the preparation method of the porous sustained-release carrier includes the following steps: adding a water glass solution to a filler mixture, wherein the filler mixture includes fly ash, kaolin and zeolite powder, mixing, granulating and forming, and calcining at 400-500°C for 2-3h to obtain a porous sustained-release carrier; the mass ratio of the fly ash, kaolin, zeolite powder and water glass is 5-7:3-5:2-4:3-4; the mass fraction of the water glass solution is 30-40%.
[0055] In some specific embodiments, the nutrients include the following components by weight: 25-35 parts of polyhydroxybutyrate valerate (PHBV), 65-75 parts of acetate starch, 15-25 parts of butyric acid, 4-8 parts of MnSO4, 4-8 parts of MgSO4, 2-5 parts of ZnSO4, 0.01-0.05 parts of CuSO4, 0.2-0.4 parts of KI, and 0.01-0.03 parts of CaCl2.
[0056] In some specific embodiments, the inner ball cage is an openable and closable sphere composed of an inner upper ball cage and an inner lower ball cage, and the outer ball cage is an openable and closable sphere composed of an outer upper ball cage and an outer lower ball cage; an annular upper partition net and a lower partition net are provided between the outer upper ball cage and the outer lower ball cage; the outer ring side and the inner ring side of the upper partition net are respectively connected to the inner wall of the outer upper ball cage and the outer wall of the inner upper ball cage; the outer ring side and the inner ring side of the lower partition net are respectively connected to the inner wall of the outer lower ball cage and the outer wall of the inner lower ball cage.
[0057] The application of the water quality improvement device in microbial water treatment comprises the following steps: placing the water quality improvement device in a water treatment device, performing water treatment after biofilm formation, wherein during the biofilm formation and water treatment process, the temperature is controlled not to be higher than 30°C and the pH is controlled not to be lower than 5.0; when the water treatment efficiency decreases, taking out the solid composite carbon source in the water quality improvement device, reloading the nutrients according to step (3), reloading the water quality improvement device, and placing the water quality improvement device in the water treatment device again for water treatment.
[0058] Preparation Example 1
[0059] The solid composite carbon source is prepared by the following steps:
[0060] Step 1 (preparation of porous sustained-release carrier):
[0061] The following raw materials were weighed by weight: 28 parts of fly ash, 20 parts of kaolin, 15 parts of zeolite powder, and 16 parts of water glass; the water glass was dissolved in water to prepare a 35wt% water glass solution for later use. The fly ash, kaolin, and zeolite powder were added to a mixer, stirred evenly, and then the water glass solution was added and stirred evenly, and then formed into spheres with a diameter of about 2.5 cm, dried at room temperature, and calcined at 500°C for 2 hours to obtain a porous sustained-release carrier.
[0062] Step 2 (Bromination):
[0063] The silane coupling agent KH550 and 90% vol ethanol aqueous solution were mixed at a mass ratio of 1:5, and stirred at 40°C for 1 hour to obtain a hydrolyzate. A porous sustained-release carrier having the same mass as KH550 was weighed and added to the hydrolyzate, stirred at 75°C for 3 hours, filtered, and the precipitate was washed with ethanol and water in turn, and dried to obtain an amino-modified porous sustained-release carrier.
[0064] The aminated porous sustained-release carrier, 2-bromoisobutyryl bromide, acid-binding agent and N,N-dimethylacetamide were weighed in a mass ratio of 1:1.5:2:5. 2-Bromoisobutyryl bromide and triethylamine were added to N,N-dimethylacetamide and mixed well, then the aminated porous carrier was added, stirred for 5 hours in an ice bath (0-2°C), and filtered to obtain a brominated porous carrier.
[0065] Step 3 (Grafting the Switching Polymer):
[0066] The brominated porous sustained-release carrier, NIPAAm, 4VP, CuBr and pentamethyldiethylenetriamine (PMDETA) were weighed according to a mass ratio of 1:1.5:0.1:0.5:0.8; NIPAAm and 4VP were prepared into 10wt% NIPAAm solution and 10wt% 4VP solution respectively using acetone as solvent for standby use. The brominated porous carrier was added to acetone according to a mass ratio of 1:30, and then CuBr and PMDETA were added, and after mixing, nitrogen was introduced for 10 minutes to exhaust the air, and the NIPAAm solution was added, and after stirring at 35°C for 2 hours, the 4VP solution was added, and the stirring was continued at 35°C for 15 minutes, and the precipitate was washed with water and dried to obtain a nutrient sustained-release carrier.
[0067] Step 4 (Loading Nutrients):
[0068] The following raw materials were weighed by weight: 32 parts of PHBV, 70 parts of acetate starch, 20 parts of butyric acid, 4 parts of MnSO4, 5 parts of MgSO4, 3.5 parts of ZnSO4, 0.02 parts of CuSO4, 0.3 parts of KI, 0.02 parts of CaCl2, and 400 parts of ethyl acetate. After mixing all the raw materials, the pH was adjusted to 3.5, the temperature was raised to 40°C, 15% of the weight of the nutrient slow-release carrier was added, and after standing at 40°C for 12 hours, the pH was adjusted to 7.5, and the mixture was naturally cooled to room temperature (26°C), filtered, and dried to obtain a solid composite carbon source.
[0069] Preparation Example 2
[0070] The solid composite carbon source is prepared by the following steps:
[0071] Step 1 (preparation of porous sustained-release carrier):
[0072] The following raw materials were weighed by weight: 28 parts of fly ash, 20 parts of kaolin, 15 parts of zeolite powder, and 16 parts of water glass; the water glass was dissolved in water to prepare a 35wt% water glass solution for later use. The fly ash, kaolin, and zeolite powder were added to a mixer, stirred evenly, and then the water glass solution was added and stirred evenly, and then formed into spheres with a diameter of about 2.5 cm, dried at room temperature, and calcined at 500°C for 2 hours to obtain a porous sustained-release carrier.
[0073] Step 2 (Bromination):
[0074] After mixing silane coupling agent KH550 and 90% vol ethanol aqueous solution in a mass ratio of 1:7.5, the mixture was stirred at 45°C for 1.5 hours to obtain a hydrolyzate. A porous sustained-release carrier with a mass of 75% of KH550 was weighed and added to the hydrolyzate, stirred at 80°C for 2 hours, filtered, and the precipitate was washed with ethanol and water in turn, and dried to obtain an amino-modified porous sustained-release carrier.
[0075] The aminated porous sustained-release carrier, 2-bromoisobutyryl bromide, acid-binding agent and N,N-dimethylacetamide were weighed in a mass ratio of 1:2:4:10. 2-bromoisobutyryl bromide and triethylamine were added to N,N-dimethylacetamide and mixed well, and then the aminated porous carrier was added, stirred for 6 hours in an ice bath (0-2°C), and filtered to obtain a brominated porous carrier.
[0076] Step 3 (Grafting the Switching Polymer):
[0077] The brominated porous sustained-release carrier, NIPAAm, 4VP, CuBr and PMDETA were weighed in a mass ratio of 1:2.0:0.1:0.5:0.8; NIPAAm and 4VP were prepared into 10wt% NIPAAm solution and 10wt% 4VP solution respectively using acetone as solvent for standby use. The brominated porous carrier was added to acetone in a mass ratio of 1:30, and then CuBr and PMDETA were added, and after mixing, nitrogen was introduced for 10 minutes to exhaust the air, and the NIPAAm solution was added, and after stirring at 40°C for 2 hours, the 4VP solution was added, and the stirring was continued at 40°C for 15 minutes, and the precipitate was washed with water and dried to obtain a nutrient sustained-release carrier.
[0078] Step 4 (Loading Nutrients):
[0079] The following raw materials were weighed by weight: 32 parts of PHBV, 70 parts of acetate starch, 20 parts of butyric acid, 4 parts of MnSO4, 5 parts of MgSO4, 3.5 parts of ZnSO4, 0.02 parts of CuSO4, 0.3 parts of KI, 0.02 parts of CaCl2, and 400 parts of ethyl acetate. After mixing all the raw materials, the pH was adjusted to 4.2, the temperature was raised to 45°C, 15% of the weight of the nutrient slow-release carrier was added, and after standing at 45°C for 10 hours, the pH was adjusted to 7.5, and the mixture was naturally cooled to room temperature (26°C), filtered, and dried to obtain a solid composite carbon source.
[0080] Preparation Example 3
[0081] The solid composite carbon source is prepared by the following steps:
[0082] Step 1 (preparation of porous sustained-release carrier):
[0083] The following raw materials were weighed by weight: 28 parts of fly ash, 20 parts of kaolin, 15 parts of zeolite powder, and 16 parts of water glass; the water glass was dissolved in water to prepare a 35wt% water glass solution for later use. The fly ash, kaolin, and zeolite powder were added to a mixer, stirred evenly, and then the water glass solution was added and stirred evenly, and then formed into spheres with a diameter of about 2.5 cm, dried at room temperature, and calcined at 500°C for 2 hours to obtain a porous sustained-release carrier.
[0084] Step 2 (Bromination):
[0085] After mixing silane coupling agent KH550 and 90% vol ethanol aqueous solution in a mass ratio of 1:4.5, the mixture was stirred at 50°C for 0.5h to obtain a hydrolyzate. A porous sustained-release carrier with a mass 1.4 times that of KH550 was weighed and added to the hydrolyzate, stirred at 70°C for 4h, filtered, and the precipitate was washed with ethanol and water in turn, and dried to obtain an amino-modified porous sustained-release carrier.
[0086] The aminated porous sustained-release carrier, 2-bromoisobutyryl bromide, acid-binding agent and N,N-dimethylacetamide were weighed in a mass ratio of 1:0.8:1.6:5. 2-bromoisobutyryl bromide and triethylamine were added to N,N-dimethylacetamide and mixed well, then the aminated porous carrier was added, stirred for 4 hours in an ice bath (0-2°C), and filtered to obtain a brominated porous carrier.
[0087] Step 3 (Grafting the Switching Polymer):
[0088] The brominated porous sustained-release carrier, NIPAAm, 4VP, CuBr and PMDETA were weighed in a mass ratio of 1:2.0:0.2:0.3:0.6; NIPAAm and 4VP were prepared into 10wt% NIPAAm solution and 10wt% 4VP solution respectively using acetone as solvent for standby use. The brominated porous carrier was added to acetone in a mass ratio of 1:30, and then CuBr and PMDETA were added, and after mixing, nitrogen was introduced for 10 minutes to exhaust the air, and the NIPAAm solution was added, and after stirring at 30°C for 2.5 hours, the 4VP solution was added, and the stirring was continued at 30°C for 20 minutes, and the precipitate was washed with water and dried to obtain a nutrient sustained-release carrier.
[0089] Step 4 (Loading Nutrients):
[0090] The following raw materials were weighed by weight: 32 parts of PHBV, 70 parts of acetate starch, 20 parts of butyric acid, 4 parts of MnSO4, 5 parts of MgSO4, 3.5 parts of ZnSO4, 0.02 parts of CuSO4, 0.3 parts of KI, 0.02 parts of CaCl2, and 400 parts of ethyl acetate. After mixing all the raw materials, the pH was adjusted to 3.0, the temperature was raised to 38°C, 15% of the weight of the nutrient slow-release carrier was added, and after standing at 38°C for 14 hours, the pH was adjusted to 7.5, and the mixture was naturally cooled to room temperature (26°C), filtered, and dried to obtain a solid composite carbon source.
[0091] Preparation Example 4
[0092] The difference between this preparation example and preparation example 1 is that step 4 is replaced by:
[0093] The following raw materials were weighed by weight: 32 parts of PHBV, 70 parts of acetate starch, 20 parts of butyric acid, 4 parts of MnSO4, 5 parts of MgSO4, 3.5 parts of ZnSO4, 0.02 parts of CuSO4, 0.3 parts of KI, 0.02 parts of CaCl2, and 400 parts of ethyl acetate. After all the raw materials were mixed, the pH was adjusted to 7.5, and 15% of the weight of the nutrient slow-release carrier was added. After standing at 40°C for 12 hours, the solid composite carbon source was obtained by filtering and drying.
[0094] Preparation Example 5
[0095] The difference between this preparation example and preparation example 1 is that step 3 is replaced by:
[0096] The brominated porous sustained-release carrier, NIPAAm, 4VP, CuBr and pentamethyldiethylenetriamine (PMDETA) were weighed in a mass ratio of 1:1.6:0.5:0.8; NIPAAm was prepared into a 10wt% NIPAAm solution using acetone as a solvent for later use. The brominated porous carrier was added to acetone in a mass ratio of 1:30, and then CuBr and PMDETA were added, mixed, nitrogen was introduced for 10 minutes to exhaust the air, NIPAAm solution was added, stirred at 35°C for 135 minutes, filtered, the precipitate was washed with water, and dried to obtain a nutrient sustained-release carrier.
[0097] Preparation Example 6
[0098] The difference between this preparation example and preparation example 1 is that step 3 is replaced by:
[0099] The brominated porous sustained-release carrier, NIPAAm, 4VP, CuBr and pentamethyldiethylenetriamine (PMDETA) were weighed in a mass ratio of 1:1.5:0.1:0.5:0.8; NIPAAm and 4VP were prepared into a monomer solution using acetone as a solvent, wherein the mass fraction of NIPAAm was 10wt%, and the solution was set aside. The brominated porous carrier was added to acetone in a mass ratio of 1:30, and then CuBr and PMDETA were added, and after mixing, nitrogen was introduced for 10 minutes to exhaust the air, and the monomer solution was added, and the mixture was stirred at 35°C for 135 minutes, filtered, and the precipitate was washed with water and dried to obtain a nutrient sustained-release carrier.
[0100] Example 1
[0101] The solid composite carbon source obtained in Preparation Example 1 is loaded into a water quality improvement device. The structure of the water quality improvement device is as follows: Figure 1 and 2 As shown, the details are as follows:
[0102] The water quality improvement device is composed of an inner ball cage and an outer ball cage. The outer ball cage is set outside the inner ball cage, and the ball centers of the two overlap. The outer ball cage is an openable and closable sphere composed of an outer upper ball cage and an outer lower ball cage, and the inner ball cage is an openable and closable sphere composed of an inner upper ball cage and an inner lower ball cage. A hinge and a buckle connection are arranged between the lower edge of the outer upper ball cage and the upper edge of the outer lower ball cage. An annular upper and lower partition nets are arranged between the outer upper ball cage and the outer lower ball cage. The inner ring side of the upper partition net is fixed to the outer wall of the inner upper ball cage by welding, and the outer ring side of the upper partition net and the inner wall of the outer upper ball cage are a detachable snap-fit structure. Similar to the upper partition net, the inner ring side of the lower partition net is fixed to the outer wall of the inner lower ball cage by welding, and the outer ring side of the lower partition net and the inner wall of the outer lower ball cage are a detachable snap-fit structure. The diameters of the inner and outer ball cages are 15 cm and 50 cm respectively. The inner and outer cages and the upper and lower partitions are all provided with hexagonal through holes distributed in a honeycomb pattern, each with a side length of 1 cm. The solid composite carbon source is loaded into the inner cage, and the MBBR filler is loaded between the inner cage and the outer cage.
[0103] The water quality improvement device of this embodiment is used to carry out simultaneous nitrification and denitrification treatment of wastewater. The wastewater source is the production wastewater of a pharmaceutical factory, and the total nitrogen content (TN value) is 128 mg / L. The specific steps are as follows:
[0104] (1) First use: every 5m 2 The water quality improvement device was placed in the microbial treatment pool with a dosage of one, and the wastewater to be treated was passed into the microbial treatment pool. During this period, the pH of the influent was maintained at 7.8-8.2, the water temperature was 24-26°C, the dissolved oxygen (DO) content was 0.5-0.6 mg / L, the hydraulic retention time was 5 hours, and it was operated for 2 cycles per day to monitor the effluent TN value. The timing started from one week after the TN removal rate stabilized. The TN removal rate was 87.7%-90.5% in the first month, and 79.3%-88.9% in the sixth month, indicating that the water quality improvement device has a long validity period.
[0105] (2) Re-use: After 6 months, the water quality improvement device was opened, the solid composite carbon source was taken out, and after cleaning, the nutrients were reloaded according to step 4 in preparation example 1, and then loaded into the water quality improvement device again for simultaneous nitrification and denitrification of wastewater (the steps are the same as the first use). It was measured that the TN removal rate was 87.4-91.2% in the first month, and the TN removal rate was 77.0-84.8% in the sixth month, indicating that the solid composite carbon source can still maintain good function when reused.
[0106] Example 2
[0107] The solid composite carbon source obtained in Preparation Example 2 is loaded into a water quality improvement device, and the structure of the water quality improvement device is the same as that of Example 1.
[0108] The water quality improvement device of this embodiment is used to carry out simultaneous nitrification and denitrification treatment of wastewater. The source of the wastewater is the same as that of Example 1. The specific steps are as follows:
[0109] (1) First use: every 5m 2 The water quality improvement device was placed in the microbial treatment pool with a dosage of one, and the wastewater to be treated was passed into the microbial treatment pool. During this period, the pH of the influent was maintained at 7.8-8.2, the water temperature was 24-26°C, the dissolved oxygen (DO) content was 0.5-0.6 mg / L, the hydraulic retention time was 5 hours, and it was operated for 2 cycles per day to monitor the effluent TN value. The timing started from one week after the TN removal rate stabilized. The TN removal rate was 87.3-92.3% in the first month, and 82.6-88.2% in the sixth month, indicating that the water quality improvement device has a long validity period.
[0110] (2) Re-use: After 6 months, the water quality improvement device was opened, the solid composite carbon source was taken out, and after cleaning, the nutrients were reloaded according to step 4 in preparation example 2, and then loaded into the water quality improvement device again for simultaneous nitrification and denitrification of wastewater (the steps were the same as the first use). It was measured that the TN removal rate was 84.8-90.7% in the first month, and the TN removal rate was 80.3-85.9% in the sixth month, indicating that the solid composite carbon source can still maintain good function when reused.
[0111] Example 3
[0112] The solid composite carbon source obtained in Preparation Example 3 is loaded into a water quality improvement device, and the structure of the water quality improvement device is the same as that of Example 1.
[0113] The water quality improvement device of this embodiment is used to carry out simultaneous nitrification and denitrification treatment of wastewater. The source of the wastewater is the same as that of Example 1. The specific steps are as follows:
[0114] (1) First use: every 5m 2 The water quality improvement device was placed in the microbial treatment pool with a dosage of one, and the wastewater to be treated was passed into the microbial treatment pool. During this period, the pH of the influent was maintained at 7.8-8.2, the water temperature was 24-26°C, the dissolved oxygen (DO) content was 0.5-0.6 mg / L, the hydraulic retention time was 5 hours, and it was operated for 2 cycles per day to monitor the effluent TN value. The timing started from one week after the TN removal rate stabilized. The TN removal rate was 86.0%-90.1% in the first month, and 80.2%-86.4% in the sixth month, indicating that the water quality improvement device has a long validity period.
[0115] (2) Re-use: After 6 months, the water quality improvement device was opened, the solid composite carbon source was taken out, and after cleaning, the nutrients were reloaded according to step 4 in preparation example 3, and then loaded into the water quality improvement device again for simultaneous nitrification and denitrification of wastewater (the steps were the same as the first use). It was measured that the TN removal rate was 85.5-90.5% in the first month, and the TN removal rate was 76.2-85.0% in the sixth month, indicating that the solid composite carbon source can still maintain good function when reused.
[0116] Comparative Example 1
[0117] The solid composite carbon source obtained in Preparation Example 4 is loaded into a water quality improvement device, and the structure of the water quality improvement device is the same as that of Example 1.
[0118] The water quality improvement device of this comparative example is used to carry out simultaneous nitrification and denitrification treatment of wastewater, and the wastewater source and specific steps are the same as those in Example 1. It is measured that when used for the first time, the TN removal rate in the first month is 68.0-74.9%, and the TN removal rate in the sixth month is 24.6-27.8%.
[0119] Compared with Example 1, the TN removal rate of Comparative Example 1 is significantly reduced, indicating that in the solid composite carbon source used in the present invention, the temperature and pH response characteristics of the switch polymer can be used to increase the loading amount of nutrients and achieve a better slow-release effect. This is because: at the pH and temperature when loading nutrients, the pyridine group at the free end of the switch polymer is positively charged, and the poly N-isopropylacrylamide molecular chain shrinks, so that the pores on the porous slow-release carrier are open, and the nutrients can be loaded into the porous slow-release carrier more quickly; at the pH and temperature when water treatment (simultaneous nitrification and denitrification) is carried out, the pyridine group is uncharged, the poly N-isopropylacrylamide molecular chain stretches, and the pores on the porous slow-release carrier are closed, so that the nutrients can be slowly released when the water quality improvement device is used.
[0120] Comparative Example 2
[0121] The solid composite carbon source obtained in Preparation Example 5 is loaded into a water quality improvement device, and the structure of the water quality improvement device is the same as that of Example 1.
[0122] The water quality improvement device of this comparative example is used to carry out simultaneous nitrification and denitrification treatment of wastewater, and the wastewater source and specific steps are the same as those in Example 1. It is measured that when used for the first time, the TN removal rate in the first month is 84.7-88.2%, and the TN removal rate in the sixth month is 66.7-73.4%.
[0123] Compared with Example 1, the TN removal rate of Comparative Example 2 is significantly reduced, indicating that doping 4-vinylpyridine at the free end of the switch polymer can improve the water treatment efficiency when the solid composite carbon source is used. This is because: at the pH when the nutrients are loaded, the nitrogen atoms in the pyridine group are positively charged, which can generate electrostatic repulsion between the switch polymer molecular chains, promote the disentanglement between the switch polymer molecular chains, and thus increase the loading amount of the nutrients; and, at the pH during water treatment, the nitrogen atoms in the pyridine group are uncharged, and will not generate electrostatic repulsion between the switch polymer molecular chains, so it will not have an excessive impact on the sustained release effect of the nutrients.
[0124] Comparative Example 3
[0125] The solid composite carbon source obtained in Preparation Example 6 is loaded into a water quality improvement device, and the structure of the water quality improvement device is the same as that of Example 1.
[0126] The water quality improvement device of this comparative example is used to carry out simultaneous nitrification and denitrification treatment of wastewater, and the wastewater source and specific steps are the same as those in Example 1. It is measured that when used for the first time, the TN removal rate in the first month is 76.0-78.6%, and the TN removal rate in the sixth month is 37.9-44.3%.
[0127] Compared with Example 1, the TN removal rate of Comparative Example 3 is significantly reduced, indicating that on the solid composite carbon source, doping 4-vinyl pyridine at the free end of the switch polymer instead of the middle can improve the water treatment efficiency when it is used. This is because: doping 4-vinyl pyridine at the free end of the switch polymer can avoid the electrostatic repulsion inside the switch polymer molecular chain when loading nutrients, thereby preventing the molecular chain from shrinking, thereby increasing the loading amount of nutrients.
[0128] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0129] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A water quality improvement device for layered loading of solid composite carbon source and suspended filler, characterized in that: It comprises an inner ball cage and an outer ball cage; the inner ball cage is arranged in the outer ball cage, a plurality of through holes are distributed on the inner ball cage and the outer ball cage, and the inner ball cage and the outer ball cage are both openable and closable spheres; the inner ball cage is loaded with a solid composite carbon source; a suspended filler is loaded between the inner ball cage and the outer ball cage; the solid composite carbon source comprises a porous sustained-release carrier, nutrients loaded in the porous sustained-release carrier and a switch polymer grafted on the outside of the porous sustained-release carrier; the two ends of the switch polymer are a free end and a fixed end respectively; the fixed end is poly-N-isopropylacrylamide, which is grafted on the porous sustained-release carrier.
2. The water quality improvement device according to claim 1, characterized in that: The free end of the switch polymer is a copolymer of N-isopropylacrylamide and 4-vinylpyridine.
3. The water quality improvement device according to claim 2, characterized in that: The preparation method of the solid composite carbon source comprises the following steps: (1) Grafting the -COC(CH3)2Br group onto the surface of the porous sustained-release carrier to obtain a brominated porous sustained-release carrier; (2) After mixing the brominated porous sustained-release carrier, polymerization catalyst, ligand and solvent III, N-isopropylacrylamide is added under the protection of inert gas, and the mixture is reacted at 30-40°C for 2-2.5 hours. Then, 4-vinylpyridine is added and the mixture is reacted at 30-40°C for 15-20 minutes. The product is separated to obtain a nutrient sustained-release carrier. (3) After the nutrients are prepared into a solution, the pH is adjusted to no higher than 4.2, the temperature is raised to no lower than 38°C, a nutrient slow-release carrier is added thereto, the temperature is maintained at no lower than 38°C for immersion, and then the pH is adjusted to no lower than 5.0, and the temperature is lowered to no higher than 30°C, the product is separated, and a solid composite carbon source is obtained.
4. The water quality improvement device according to claim 3, characterized in that: In step (2), the mass ratio of the brominated porous sustained-release carrier, N-isopropylacrylamide and 4-vinylpyridine is 1:1.5~2.0:0.1~0.
2.
5. The water quality improvement device according to claim 3, characterized in that: The specific process of step (1) includes the following steps: (1.1) utilizing the hydroxyl groups on the surface of the porous sustained-release carrier to graft the aminosilane coupling agent onto the surface of the porous sustained-release carrier; (1.2) Using the aminated porous sustained-release carrier and 2-bromoisobutyryl bromide as raw materials, a substitution reaction between the amino group and 2-bromoisobutyryl bromide is carried out to obtain a brominated porous sustained-release carrier.
6. The water quality improvement device according to claim 1, characterized in that: The preparation method of the porous sustained-release carrier comprises the following steps: adding water glass solution to a filler mixture, wherein the filler mixture comprises fly ash, kaolin and zeolite powder, mixing, granulating and forming, and calcining to obtain the porous sustained-release carrier.
7. The water quality improvement device according to claim 1, characterized in that: The nutrients include the following components by weight: 25-35 parts of polyhydroxybutyrate valerate, 65-75 parts of acetate starch, 15-25 parts of butyric acid, 4-8 parts of MnSO4, 4-8 parts of MgSO4, 2-5 parts of ZnSO4, 0.01-0.05 parts of CuSO4, 0.2-0.4 parts of KI, and 0.01-0.03 parts of CaCl2.
8. The water quality improvement device according to claim 1, characterized in that: The inner ball cage is an openable and closable sphere composed of an inner upper ball cage and an inner lower ball cage, and the outer ball cage is an openable and closable sphere composed of an outer upper ball cage and an outer lower ball cage; an annular upper partition net and a lower partition net are arranged between the outer upper ball cage and the outer lower ball cage; the outer ring side and the inner ring side of the upper partition net are respectively connected to the inner wall of the outer upper ball cage and the outer wall of the inner upper ball cage; the outer ring side and the inner ring side of the lower partition net are respectively connected to the inner wall of the outer lower ball cage and the outer wall of the inner lower ball cage.
9. Use of the water quality improvement device as claimed in any one of claims 1 to 8 in microbial water treatment.
10. The use according to claim 9, characterized in that The following steps are involved: The water quality improvement device is placed in a water treatment device, and after the biofilm is formed, water treatment is performed. During the biofilm formation and water treatment process, the temperature is controlled not to be higher than 30° C. and the pH is controlled not to be lower than 5.
0. When the water treatment efficiency decreases, the solid composite carbon source in the water quality improvement device is taken out, the nutrients are reloaded according to step (3), and the solid composite carbon source is loaded into the water quality improvement device again, and the solid composite carbon source is placed in the water treatment device again for water treatment.
Citation Information
Patent Citations
Biological filler for integrated sewage treatment equipment
CN218146035U
Thermosensitive salt-releasing material as well as preparation method and application thereof
CN104861928A
Preparation method for temperature-and-pH-responsive intelligent switch film with core-shell structure microgel as switch
CN110538618A